Characterisation of Pectobacterium carotovorum causing soft rot on Kalanchoe gastonis-bonnierii in Malaysia - Golkhandan, Elham; Sijam, Kamaruzaman; Meon, Sariah; Mior Ahmad, Zainal Abidin; Nasehi, Abbas (Taylor & Francis, 2013)
Soft rot disease can be found worldwide on fleshy storage tissues of fruits, vegetables and ornamentals. The soft rot Pectobacterium carotovorum subsp. carotovorum (Pcc) is an important pathogen of Kalanchoe spp. and other ornamental plants. The disease occurs on crops in the field, greenhouses and during transit, resulting great economic damages. The economic importance of crop loss by soft rot bacteria varies by severity of the disease and value of the crop. A destructive disease on Kalanchoe gastonis-bonnierii was observed in commercial ornamental plant greenhouses in Cameron highland and Melaka, Malaysia in 2011. Samples suspected to be infested with Pectobacterium spp. were brought to the laboratory. In pathogenicity test, a suspension of 106 CFU/ml of strains was able to cause soft rot on leaves and stems. A 434 bp banding pattern on 1% agarose gel was produced in polymerase chain reaction (PCR) amplification of pectate lyase encoding gene (Pel gene). PCR amplification of the intergenic transcribed spacer (ITS) (16S–23S rRNA) ITS region with G1 and L1 primers produced two main bands at about 540 and 570 bp. The ITS-PCR products were digested with RsaI restriction enzyme. For discrimination of the P. carotovorum subsp. carotovorum (Pcc) from P. carotovorum subsp. odoriferum (Pco), all isolates subjected to α-methyl glucoside test. All isolates were identified as Pcc based on phenotypic and molecular methods. This is the first report of soft rot disease caused by P. carotovorum subsp. carotovorum on K. gastonis-bonnierii, in Malaysia.